2019
DOI: 10.1371/journal.pone.0220400
|View full text |Cite
|
Sign up to set email alerts
|

Day and night use of habitats by northern pintails during winter in a primary rice-growing region of Iberia

Abstract: Loss of natural wetlands is a global phenomenon that has severe consequences for waterbird populations and their associated ecosystem services. Although agroecosystems can reduce the impact of natural habitat loss, drivers of use of such artificial habitats by waterbirds remain poorly understood. Using the cosmopolitan northern pintail Anas acuta as a model species, we monitored home-range and fine-scale resource selection across the agricultural landscape. Individuals were tracked using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 80 publications
1
12
0
Order By: Relevance
“…We excluded data from the first 7 days after marking to avoid any effects of capture and tagging (Kuang et al, 2019), and excluded records from the last 7 days before the departure date of the spring migration because of potentially different habitat use and behaviors before migration (Papers et al, 2008). We defined migration as all locations >50 km away from the study area, and/ or ducks moving in one direction at >20 km/hr (Chan et al, 2019).…”
Section: Duck Distributions and Overlap With Wind Turbinesmentioning
confidence: 99%
“…We excluded data from the first 7 days after marking to avoid any effects of capture and tagging (Kuang et al, 2019), and excluded records from the last 7 days before the departure date of the spring migration because of potentially different habitat use and behaviors before migration (Papers et al, 2008). We defined migration as all locations >50 km away from the study area, and/ or ducks moving in one direction at >20 km/hr (Chan et al, 2019).…”
Section: Duck Distributions and Overlap With Wind Turbinesmentioning
confidence: 99%
“…The presence of resident and migratory birds in plantation areas and their surroundings is very common. These areas serve both as feeding and resting grounds for many avian species, in large part due to the loss of their natural habitats, such as natural wetlands, on which waterbird species depend throughout their life cycle [ 166 ]. Most commonly, the presence of birds in cultivation areas results in conflict, with economic losses in agriculture, such as the case of wine grapes in single vineyards [ 167 ].…”
Section: Use Of Crop Areas and Adjacent Areas By Birdsmentioning
confidence: 99%
“…This is a potential route of exposure to azole resistant strains. The contamination of these environments can also occur through an alternative route: the migratory routes of birds is a potentially important route for the dispersion of resistant strains [ 166 , 179 ], as we will discuss next.…”
Section: Use Of Crop Areas and Adjacent Areas By Birdsmentioning
confidence: 99%
See 1 more Smart Citation
“…They are considered to be good environ-mental indicators, and form the primary focus of EIAs during risk evaluations for wind farms [25]. Although mortality rates of ducks are minimal throughout the world [14,23], they inhabit shallow, subtidal coastal regions and carry out local movements between foraging sites (inland artificial wetlands) and roosting sites (the intertidal zone) [32,33], which may overlap with onshore wind farms in coastal wetlands [17]. One study using direct observations in offshore areas showed that ducks had reduced the number of landings and flights in proximity to wind turbines [34].…”
Section: Introductionmentioning
confidence: 99%